Development of Jurisprudence Learning Media for Android-based Islamic Economics at SMK Muhammadiyah Karangmojo - Yarudin, Yarudin; Arqam, Mhd Lailan; Wantini, Wantini; Perawironegoro, Djamaluddin; Yusmaliana, Desfa (ISTAWA, 2022)
The development of fiqh learning media for android-based Islamic economics at SMK Muhammadiyah Karangmojo was the focus of this research against the background that there were still many PAI learning methods, especially fiqh, using conventional methods. This study aims to describe the learning of fiqh in class XI at SMK Muhammadiyah Karangmojo and the development of fiqh media for android-based Islamic economics at SMK Muhammadiyah Karangmojo. This research applied the type of R&D research with the Borg & Gall model because it was expected to develop learning products. The research methods were model development, development procedures, and product testing. The model developed in this research was developing Islamic economics material based on Islamic Jurisprudence learning media. The results of this study indicate: (1) Fiqh learning class XI at SMK Muhammadiyah Karangmojo still uses conventional methods. There are still few teaching media for fiqh. There are 90% of students have android phones. Principals, teachers, and students expect innovation in learning media development. (2) Development of Android-based Islamic Economics Jurisprudence media. Media assessment in the form of material expert validation got a score of 73%, a fairly decent score, media experts got a score of 80% with a decent value, and the assessment of respondents in the small and medium stage usage test got a score of 90 with very good criteria to be used as class fiqh learning media XI SMK Muhammadiyah Karangmojo.